Efficacy and safety of hypertonic dextrose prolotherapy for patients with post-herpetic neuralgia - YIN Qin; CHEN Liping; XU Heng; YUAN Yan; LIANG Dong; SHEN Wen (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2024)
Objective·To investigate the efficacy and safety of hypertonic dextrose prolotherapy (DPT) in the treatment of postherpetic neuralgia.Methods·Seventy-eight patients with postherpetic neuralgia who visited the Department of Pain of The Affiliated Hospital of Xuzhou Medical University from June 2019 to December 2022 were selected. The patients were randomly assigned to a control group and a research group in a 1∶1 ratio, with 39 patients in each group. The control group was treated with traditional analgesic solution, while the research group was treated with traditional analgesic solution combined with DPT. Visual analog scale (VAS) was used to evaluate the patients' pain level before and after treatment, flow cytometry was used to measure the patients' T-cell subsets, and enzyme-linked immunosorbent assay (ELISA) was used to measure the levels of C-reactive protein (CRP), interleukin-6 (IL-6), and IL-10 cytokines. The VAS scores were compared between the two groups of patients before and at 1, 2, 4, 8, and 12 weeks after treatment. CD4+/CD8+, CRP, IL-6, IL-10 levels, and the incidence of adverse reactions before and 2 weeks after treatment were compared between the two groups.Results·There was no statistically significant difference in sex ratio, age, and disease duration between the two groups of patients. The VAS scores of the two groups of patients at 1, 2, 4, 8, and 12 weeks after treatment were significantly lower than those before treatment, and the differences were statistically significant (all P<0.05). The VAS scores of the research group at 1, 2, 4, 8, and 12 weeks after treatment were significantly lower than those of the control group (all P<0.05). There was no statistically significant difference in basal CD4+/CD8+, CRP, IL-6 and IL-10 levels between the two groups of patients. IL-6 and CRP levels in the research group were significantly lower after treatment than those in the control group, and the differences were statistically significant (all P=0.000). CD4+/CD8+ and IL-10 levels were significantly higher in the research group than those in the control group after treatment, and the difference was statistically significant (all P=0.000). No adverse reactions such as local nerve damage, epidural hematoma, infection, pneumothorax or allergy occurred in both groups of patients during the treatment.Conclusion·DPT can significantly reduce the pain of PHN patients, improve patients' T lymphocyte subpopulations and cytokine expression, and can be safely applied to the clinic.